SITOTOKSISITAS EKSTRAK ETANOL 70% KULIT JENGKOL (ARCHIDENDRON JIRINGA (JACK). I.C. NIELSEN) TERHADAP PENGHAMBATAN SEL KANKER PAYUDARA MCF-7 DAN KANKER SERVIKS HELA: Cytotoxicity Extract Ethanol 70% of Jengkol Skin (Archidendron jiringa (Jack). I.C. Nielsen) Against the Inhibition of Breast Cancer Cell MCF-7 and Cervical Cancer HeLa - Harry Noviardi; Antonius Padua Ratu; Diah Ajeng Tri R (Jurnal Ilmiah Manuntung, 2019)
Jengkol (Archidendron jiringa (Jack).I.C. Nielsen) skin for this belongs to the organic wastes that do not provide economic value. Compounds of natural ingredients on the Jengkol Skin among others, alkaloids, flavonoids, tannins, saponins, and triterpenoids. Some of the molecular structures of the compound are thought to potentially in inhibiting the growth of cancer cells. This research aimed to determine the cytotoxicity effect of 70% ethanol extract of Jengkol Skin as anticancer. Jengkol Skin was macerated in ethanol 70% then extract was concentrated with a rotary vacuum evaporator and water bath. Cytotoxicity test was carried out using cells MCF-7 (breast cancer) and HeLa cells (cervical cancer) based upon the method of MTT assay. The parameter was the value measured inhibition concentration (IC50). Extracts of the Jengkol Skin showed activity against cytotoxicity MCF-7 cells with IC50 values of 51.76 μg/mL and for the IC50 value of HeLa cells 39.618 μg/mL. IC50 values of the cell were less than 100 μg/mL, indicated categories of potential cytotoxicity. The Jengkol Skin extract could be used as anticancer agents.